Cholestatic drug induced liver injury in active pulmonary tuberculosis patient: a case report - Theodora, Agnes; Suryana, Ketut (International Journal of Advances in Medicine, 2022)
Drug induced liver injury (DILI) has been a long-standing concern in the treatment of tuberculosis. Anti-tuberculosis therapy (ATT) is known to have hepatotoxicity effect. DILI is diagnosed clinically using liver biochemical test, such as alanine transaminase (ALT), alkaline phosphatase (ALP), and total bilirubin. Calculating ratio (R) of ALT over ALP, is useful to classify types of injury pattern in DILI. Roussel Uclaf causality assessment method (RUCAM) scale serves as a method to assess the causality agents for DILI. Here we report a case of 59 years old male who developed cholestatic DILI on fourth weeks of ATT. Patient came in with loss of consciousness, jaundice, nausea, pruritus, and abdominal tenderness. Patient’s ALT level was normal, but ALP and total bilirubin was significantly elevated, with R values less than 2, indicating a cholestatic type of injury. Patient sputum was positive for tuberculosis bacteria, showing an active infection. Patient was admitted and ATT was discontinued. Patient showed improvement, but eventually fall into sepsis and developed respiratory distress on sixth day of admission despite adequate treatment and close monitoring. Despite most of the cases resolves spontaneously upon cessation of the toxic agents, in the severe form, it may fall into chronic liver injury, acute liver failure, and eventually death. Preventing DILI is readily important by educating, screening for risk factors, and routine evaluation of liver enzymes in patient under ATT. Early diagnosis and prompt treatment are needed to avoid poor prognosis in the course of the disease.